The neural basis of deficient response inhibition in children with neurofibromatosis type 1: Evidence from a functional MRI study. (August 2017) - Pride, Natalie A.; Korgaonkar, Mayuresh S.; North, Kathryn N.; Barton, Belinda; Payne, Jonathan M.
Abstract: Impaired response inhibition is a predominant feature of several neuropsychiatric disorders; in general the underlying aetiology of these disorders and associated impairments is unknown. The common occurrence of impaired response inhibition in a single gene disorder such as neurofibromatosis type 1 (NF1), provides a valuable opportunity to explore its mechanistic basis through the study of gene–brain–behaviour interactions. We used functional brain imaging with a Go/No–Go task to examine the neural substrates of response inhibition in children with NF1 and age and gender matched typically developing subjects. Children with NF1 were found to have abnormal activation patterns in several cortical regions, with significantly reduced activation in the inferior occipital gyrus (IOG), the fusiform gyrus/posterior cerebellum (FG/PC), the pre-supplementary motor area (pre-SMA) and the inferior frontal gyrus (IFG). Importantly, activation in the right IFG was associated with faster task reaction times and impairment in sustained attention in subjects with NF1. Our study supports the hypothesis that a network of regions typically associated with response inhibition is dysfunctional in children with NF1 and suggests this dysfunction is linked to cognitive impairment in this disorder.